2010
DOI: 10.1002/hed.21342
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between reduced expression of the spindle checkpoint protein BubR1 and bad prognosis in tonsillar carcinomas

Abstract: We have shown that BubR1 expression is a novel and strong prognostic factor in tonsillar carcinomas, giving additional information to the TNM stage and other known prognostic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
0
6
1
Order By: Relevance
“…34 Our study failed to demonstrate a statistically significant correlation between Ki-67 labeling index and BUBR1 expression. This finding does not support the association between overexpression of BUBR1 and increased proliferative activity previously reported not only in gastric, 19 bladder, 21 colorectal, 17 and hepatocellular cancer, 27 but also in tonsillar carcinoma 34 ; however, it is not in contrast with our above-mentioned results that suggest a favorable role of BUBR1 in the prognosis of oral cancer. This assumption, in fact, would have been difficult to reconcile with a high proliferative index, which is a well-known negative prognostic factor in a variety of tumors, including OSCC.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…34 Our study failed to demonstrate a statistically significant correlation between Ki-67 labeling index and BUBR1 expression. This finding does not support the association between overexpression of BUBR1 and increased proliferative activity previously reported not only in gastric, 19 bladder, 21 colorectal, 17 and hepatocellular cancer, 27 but also in tonsillar carcinoma 34 ; however, it is not in contrast with our above-mentioned results that suggest a favorable role of BUBR1 in the prognosis of oral cancer. This assumption, in fact, would have been difficult to reconcile with a high proliferative index, which is a well-known negative prognostic factor in a variety of tumors, including OSCC.…”
Section: Discussioncontrasting
confidence: 60%
“…BUBR1 stained the cytoplasm of normal oral epithelial cells, as previously described by BurumAuensen et al 36 In OSCC, subcellular localization of BUBR1 remained mainly confined to the cytoplasm, confirming previous observations. 34,37 In the normal epithelium, sporadic cells in the basal and parabasal layers occasionally exhibited weak staining. In the dysplastic epithelium neighboring squamous cell carcinomas, BUBR1-positive cells were more frequent and were also detectable above the parabasal layer (see Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that upregulation of BubR1 in ovarian and tonsillar cancers was associated with lymph node metastasis, tumor grade and stage (11,25). We examined the relationship between the clinical histopathological features and BubR1 expression in the ESC cases (Table I).…”
Section: High Expression Of Bubr1 In Clinical Esophageal Cancer Samplesmentioning
confidence: 99%
“…In contrast, another study shows that overexpression of BubR1 was associated with a less advanced tumor stage, but patients with overexpression of BubR1 showed shorter recurrence-free survival than those without it, making BubR1 a promising prognostic marker in patients with OSCC [64]. Curiously, the proliferation marker Ki-67 did not demonstrate a statistical significant correlation with BubR1 expression, contrasting with a previous report in patients with tonsillar carcinomas [65]. Another SAC protein that was also found to be overexpressed in oral carcinoma is the Aurora B kinase.…”
Section: Spindle Assembly Checkpoint and Oral Squamous Cell Carcinomamentioning
confidence: 95%